2015
DOI: 10.1111/ejss.12260
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus sorption, supply potential and availability in soils with contrasting parent material and soil chemical properties

Abstract: Soil phosphorus (P) management requires a more targeted and soil-specific approach than is currently applied for agronomic recommendations and environmental evaluation. Phosphorus buffering capacities control the supply of P in the soil solution and were measured across Irish soils with contrasting parent material and chemical properties. Langmuir sorption buffer capacities (MBCs) and binding energies (b) were strongly correlated with soil pH and extractable aluminium (Al). A broken-line regression fitted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 31 publications
9
86
1
5
Order By: Relevance
“…Overall, the maximum P sorption for all of the tested substrates increased as follows: quartz sands (III < II < I < IV) < activated carbon < zeolite < ceramic < furnace slag. The results of the present study demonstrated that the P adsorption capacities of substrates vary significantly; these findings are comparable with those reported in the literature [12,[24][25][26].…”
Section: P Adsorption Capacities Of the Substratessupporting
confidence: 92%
“…Overall, the maximum P sorption for all of the tested substrates increased as follows: quartz sands (III < II < I < IV) < activated carbon < zeolite < ceramic < furnace slag. The results of the present study demonstrated that the P adsorption capacities of substrates vary significantly; these findings are comparable with those reported in the literature [12,[24][25][26].…”
Section: P Adsorption Capacities Of the Substratessupporting
confidence: 92%
“…Soil containing phosphates were usually alkaline, so it could not be absorbed by plants (Darmawijaya, 1990). This relationship was also confirmed from the research conducted by Daly et al (2015) who found a correlation between the content of Ca 2+ and P availability in the soil. A low content of K + and a high CEC soil was caused by the adsorption of heavy clay minerals type 2:1.…”
Section: Soil Characteristicssupporting
confidence: 70%
“…Phosphorus (P) is an important element for all life forms and is also an important nutrient for plant growth crop productivity (Daly et al, 2015;Stutter et al, 2012). Phosphorus application in agricultural soils may lead to accumulation of P (Delgado and Scalenghe, 2008;Sattari et al, 2012) as the approximate percent recovery of applied P for crops usually is between 10 and 25% (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, recommendations for P fertilizers are based on soil test methods and recently they were also used for environmental risk assessment Sharpley et al, 2003;Daly et al, 2015). It was indicated that the P extracted by extractants such as Olsen-P and Mehlich-3-P had correlated well with P loss via runoff and/or leaching (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%